Late Quaternary environments and prehistoric occupation in the lower White Nile valley, central Sudan. (15th December 2015) - Williams, Martin A.J.; Usai, Donatella; Salvatori, Sandro; Williams, Frances M.; Zerboni, Andrea; Maritan, Lara; Linseele, Veerle
Abstract: Despite the major contributions provided over fifty years ago by A.J. Arkell and J.D. Tothill to our understanding of late Quaternary environments and prehistoric occupation near the confluence of the Blue and White Nile in central Sudan, three key questions have remained unresolved since then. (a) Was the decline in Nile flood levels from early Holocene times onwards caused by a reduction in Nile discharge, or by channel incision, or both? (b) Was the regional climate wetter during times of high Nile floods and drier during times of low Nile floods? (c) Given the high degree of disturbance of Mesolithic and later prehistoric sites, is it possible to identify primary-context, stratified and undisturbed occupation? Drawing upon dated evidence from three sites to the east of and three to the west of the lower White Nile, we provide a qualified answer to the first question and documented affirmative answers to the second and third questions. Highlights: White Nile flood levels declined from early Holocene times onwards. One cause was a reduction in both Blue and White Nile discharge. Another cause was channel incision by the Blue Nile. The climate in central Sudan was wetter during times of high White Nile floods. Primary-context, stratified Mesolithic sites occur west of the lower White Nile.